Racemization barriers of atropisomeric 3, 3′-bipyrroles: an experimental study with theoretical verification. Issue 75 (26th July 2016) - Chatterjee, Sourav; Butterfoss, Glenn L.; Mandal, Madhumita; Paul, Bishwajit; Gupta, Sreya; Bonneau, Richard; Jaisankar, Parasuraman
Abstract : The activation barrier of racemization was determined for atropisomeric 3, 3′-bipyrroles and they are found to be configurationally stable. Abstract : The significant rotational energy barrier about the stereogenic carbon–carbon bond of axially chiral 3, 3′-bipyrroles has been investigated by electronic circular dichroism (ECD) spectroscopy, time dependent HPLC analysis, and computational modeling. The results elucidate pathways and transition states involved in configurational inversion, thereby confirming that 3, 3′-bipyrrole derivatives can exist in stable and isolable atropisomeric forms.